2017
DOI: 10.21815/jde.017.044
|View full text |Cite
|
Sign up to set email alerts
|

Humanism in Dental Education: A Comparison of Theory, Intention, and Stakeholder Perceptions at a North American Dental School

Abstract: In today's dental education environment, a humanistic culture is an expectation for all U.S. dental schools, codified in 2013 by its inclusion in the Commission on Dental Accreditation's standards for accreditation. The University of the Pacific Arthur A. Dugoni School of Dentistry has made an active commitment to humanism since the mid-1970s. The aim of this study was to determine how well the school's students and faculty and staff members perceived the school was living up to its formal aspirational values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…4,5,9,20,[22][23][24] Our study joins the recently published one conducted at the University of the Pacific in including the perceptions of dental school staff members in assessments, affirming that working in a humanistic environment is an important issue for them as well. 25 Fourth, all three groups in our study indicated that it was not always easy for them to feel comfortable with others at the school regardless of their position. Staff respondents had the lowest satisfaction ratings in general as compared to faculty and student respondents on this issue.…”
Section: Micro-aggressions and Bullyingmentioning
confidence: 64%
“…4,5,9,20,[22][23][24] Our study joins the recently published one conducted at the University of the Pacific in including the perceptions of dental school staff members in assessments, affirming that working in a humanistic environment is an important issue for them as well. 25 Fourth, all three groups in our study indicated that it was not always easy for them to feel comfortable with others at the school regardless of their position. Staff respondents had the lowest satisfaction ratings in general as compared to faculty and student respondents on this issue.…”
Section: Micro-aggressions and Bullyingmentioning
confidence: 64%
“…Although the literature provides descriptions of strategies that have been used to increase compassionate care among healthcare professionals, there is lack of clarity on how and when to teach compassion, how to measure it, 48 and how to sustain it specifically in dentistry. Role modeling by instructors may assist in teaching a humanistic approach to care; 46,55 it may also be possible to increase compassion and empathy through communication skills training 48,56 . It does not appear that these results can be sustained long term without further intervention.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Multivalent relationships between students and educators are not a new finding, and in fact, the position of and treatment of students has been a perpetual concern of dental and other health professional education. 15,33 Professional development of educators, humanistic cultures 34 and serious calls for the professionalisation of clinical education are ways that have been proposed to help address this issue. A recent discussion paper 35 warns that the possession of a dentistry degree is not a sufficient scholarly background for effective participation in dental education.…”
Section: Multivalent Relationshipsmentioning
confidence: 99%